Evaluate the Economic Value of the Recreational Services of the Hon Yen Complex in Phu Yen Province - Thanh, Pham Viet; Ngoc, Dang Thi; Van Truong, Tran; Cao Huan, Nguyen; Vu Viet Quan, Du (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 1, 2025)
This study focuses on assessing the economic value of recreation and tourism services of the Hon Yen complex. From that, this researchdetermine the potential of recreation and tourism services and estimate the value of recreation and tourism services from domestic tourists in the study area. Authors used 135 random questionairs of tourists, 20 questionnaires of business households in the Hon Yen complex and statistical data of the working-age population of 15 provinces and cities in the country. The zonal travel cost method (ZTCM) was applied to construct demand curves, calculate the value of recreation and tourism services and quantify the total economic value of the resources and environment of the Hon Yen complex. The result showed that the recreation and tourism service value of the Hon Yen complex is 389.349,5 million VND. The value of recreation and tourism services from coral reef alone is 233.609,7 million VND. The demand curve of tourism was represented by the function VRi = 23,934 - 0,00001358*TCi. The tourists'willingness to pay for conservation and tourism development is 56.277 VND. The total of tourists' willingness to pay for the Hon Yen complex is 5.064,9 million VND. The results are the basis for proposing solutions for sustainable tourism development associated with the protection, conservation and development of the Hon Yen complex ecosystems.